The Lateral-W Construct: An Anatomical Variant of the Dorsal Wrist Ligaments - Fermín, Theodorakys Marín; Zampeli, Frantzeska; Hagert, Elisabet (Journal of Wrist Surgery, 2022)
Background The dorsal intercarpal ligament (DIC) is an elegant dorsal stabilizer of the proximal carpal row, including the scaphoid's proximal pole and scapholunate joint. Along with the dorsal radiocarpal (DRC) ligament, it acts as a dorsal radioscaphoid stabilizer, with dynamism due to its ability to modify its length up to threefold by changing the angles between its V-shaped bundle morphology. The DIC ligament consistently originates from the dorsal tubercle of the triquetrum on the ulnar side. It spans transversely, attaching to the dorsal groove of the scaphoid (97–100%), lunate (75–90%), and proximal rim of the trapezium (12.5–50%), and overlapping the lunotriquetral interosseous ligament and the scapholunate interosseous ligament. Together with the DRC, Viegas et al (Viegas SF, Yamaguchi S, Boyd NL, Patterson RM. The dorsal ligaments of the wrist: anatomy, mechanical properties, and function. J Hand Surg Am 1999;24(3):456–468) proposed that this ligament complex should be called the “lateral-V construct.”Anatomical Variant The authors present a unique type C variant of the DIC ligament, showing a distinct thick bundle directed at the dorsal aspect of the second metacarpal base that thus creates a “lateral-W construct.” This dorsal triquetro-metacarpal 2 (dTqMC2) ligament acts as restraint to the body of the capitate and will provide enhanced stability of the dorsal midcarpal joint by limiting dorsal translation of the capitate in relation to the lunate.Clinical Relevance Our finding may contribute to the increasing knowledge of the dorsal ligament complex and its role in dorsal midcarpal instability, as well as surgical repair techniques.
Keywords: wrist; dorsal ligament complex; dorsal intercarpal ligament; anatomy variations; carpal instability